Search for invisibly decaying Higgs bosons in e+e−→Z0h0 production at √s=183-209 GeV - Abbiendi, Giovanni; Bock, Peter (Physics letters, 2010)
A search is performed for Higgs bosons decaying into invisible final states, produced in association with a Z0 boson in e+e− collisions at energies between 183 and 209 GeV. The search is based on data samples collected by the OPAL detector at LEP corresponding to an integrated luminosity of about 660 pb−1. The analysis aims to select events containing the hadronic decay products of the Z0 boson and large missing momentum, as expected from Higgs boson decay into a pair of stable weakly interacting neutral particles, such as the lightest neutralino in the Minimal Supersymmetric Standard Model. The same analysis is applied to a search for nearly invisible Higgs boson cascade decays into stable weakly interacting neutral particles. No excess over the expected background from Standard Model processes is observed. Limits on the production of invisibly decaying Higgs bosons produced in association with a Z0 boson are derived. Assuming a branching ratio BR(h0→invisible)=1, a lower limit of 108.2 GeV is placed on the Higgs boson mass at the 95% confidence level. Limits on the production of nearly invisibly decaying Higgs bosons are also obtained.
Online verfügbar 14 October 2009
*OPAL Collaboration: G. Abbiendi, P. Bock [und 206 weitere Personen]
Im Titel sind die Zeichen + und - hochgestellt
Im Titel ist die Zahl 0 hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol